2017
DOI: 10.1097/mol.0000000000000441
|View full text |Cite
|
Sign up to set email alerts
|

Protein changes in non-LDL-lipoproteins in familial hypercholesterolemia: implications in cardiovascular disease manifestation and outcome

Abstract: The identification of the specific changes in HDL-associated proteins that contribute to the increased cardiovascular risk of familial hypercholesterolemia patients could be useful for the development of novel therapeutic targets. These novel strategies, in combination with current lipid-lowering therapies, may help to reduce the residual risk found in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 48 publications
0
3
0
Order By: Relevance
“…Additionally platelets can modify native HDL, resulting in a dysfunctional and pro-thrombotic form ( Blache et al, 2012 ). Patients with familiar hypercholesterolemia display reduced concentrations of apoAIV and LCAT and a truncated form of apoLI ( Cubedo et al, 2016 ; Badimon et al, 2017 ). Experimental studies showed that much of the structural modifications and impairment in HDL function are as a result of increased LDL cholesterol (LDL-C) concentrations ( Vilahur et al, 2015 ; Padró et al, 2017 ).…”
Section: Hdl Functionalitymentioning
confidence: 99%
“…Additionally platelets can modify native HDL, resulting in a dysfunctional and pro-thrombotic form ( Blache et al, 2012 ). Patients with familiar hypercholesterolemia display reduced concentrations of apoAIV and LCAT and a truncated form of apoLI ( Cubedo et al, 2016 ; Badimon et al, 2017 ). Experimental studies showed that much of the structural modifications and impairment in HDL function are as a result of increased LDL cholesterol (LDL-C) concentrations ( Vilahur et al, 2015 ; Padró et al, 2017 ).…”
Section: Hdl Functionalitymentioning
confidence: 99%
“…Recent reviews have critically addressed the role of high-density lipoprotein (HDL) in atherosclerosis development, highlighting the potential rapid movement of unesterified cholesterol (UC) from cells and triglyceride-rich particles to HDL as well as from HDL to LDL or tissues [4,5]. There is also evidence indicating that HDL remodeling, metabolism, and function, including its ability to induce macrophage cholesterol efflux, are impaired in the monogenic forms of FH [6][7][8][9][10]. Whether this impairment is intrinsic to the disease and influences the entire reverse cholesterol transport (RCT) pathway and cardiovascular risk and is corrected by current treatments is not yet well-established.…”
Section: Abbreviationsmentioning
confidence: 99%
“…Indeed, HDL composition is a key atheroprotective determinant. Decreased levels of HDL-cholesterol (HDL-C) have been consistently observed in both heterozygous FH and homozygous FH in association with HDL structural and functional abnormalities [6][7][8][9][10].…”
Section: Hdl Content and Remodeling Alterations In Fhmentioning
confidence: 99%